A Study on Disinformation, Public Sentiment, and the Significance of Critical Thinking (International Journal of Food and Nutritional Sciences, 2022)
The vulnerability of the public to the (mis-) information is a matter of concern. We aim to provide a perspective on how people decode information, and what all skill sets are required to decode information accurately as information decoding directly affects public opinion and the ways people practice critical thinking to filter the information they receive. The article describes Indian and Western perspectives about critical thinking and analyzes the psychological factors concerning misinformation and public opinion. The article further examines how external determinants such as radicalization, the filter bubble, and advertisements influence one's pre-existing opinions and have the potential to block the analytical and critical thinking of people. It was found that misinformation spreads through the creation of filter bubbles and personalized advertisements, which exploit the flaws of human cognition. Such spread of misinformation leads to radicalization, where an individual develops an extreme view biased towards just one perspective, thus compromising critical thinking skills. The article concludes that such issues can be circumvented through the individual seeking the opposing viewpoints and developing awareness about how algorithms like online cookies work. Future studies should focus on how news outlets and social media platforms can implement counter measures to crack down on content spreading (mis-)information